AL-HADIS BAYNA AL-TAJDID (DIRASAH TAHLILIYYAH HAWLA MAKANAH AL-SUNNAH 'INDA MUHAMMAD RASYID RIDHA) - Hanapi, Abdullah (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2022)
Hadith between Renewal (An Analytical Study on the Status of the Sunnah According to Muhammad Rashid Rida). The hadith studies (read: sunnah), its position and history requires research from ‘ulama, muhaddisun, ushuli because its considered tohave “historical problems” as questioned by orientalis scholars, not without reason for the historicity of the sunna, its invitation of many scholars to research the “historical traces” about tadwin al-ahadis (read: codification) in the late second and early third centuries hijriyah with this related historiography which recorded quite “uniquely” in theses of “chronology and theorization”. But long after so